Analisis Permasalahan Kredit Macet - Khofifah Indah Pohan; Mustapa Kamal Rokan (Postgraduate, University of Mataram, 2022)
This research aims to find out what factors are the cause of bad credit problems and how the bank sumut Syariah branch office medan in handling non-performing loans. The type of research conducted is qualitative research using descriptive methods. The results of the research findings show that the causes of bad credit problems are: (1) Weaknesses from the internal debtor side can be caused by bad faith from the debtor, and the decline of the debtor's business resulted in a decrease in the debtor's ability to pay installments; (2) Weaknesses from the internal side of banks/financial institutions can be caused by bad faith from bank officers/financial institutions for personal interests, such as bank employees/financial institutions repaid debtors' credits that reward the disbursement of the credit. In the case of bad loans, the bank needs to make a rescue, so that it will not cause losses. Rescues that are carried out can be by providing relief in the form of a period of return, especially for credits that have experienced disasters